Connecting Through Technology During COVID-19 - Hall, Jeffrey; Pennington, Natalie; Holmstrom, Amanda (Human Communication & Technology, 2021)
This manuscript examines the patterns of information communication technology (ICT) use with friends and family outside of the home during the COVID-19 pandemic, and the associations among ICT use and psychological (i.e., loneliness; stress) and social (i.e., social needs; relationship maintenance) wellbeing. In early May 2020, a representative panel of American adults was surveyed (N = 1,947). Results suggest that despite 90% of the sample complying with shelter-in-place (SIP) orders, face-to-face contact with friends and family outside of the home was the primary predictor of getting one’s social needs met and mitigating loneliness. In contrast with predictions drawn from media richness theory, voice calls were associated with less stress, loneliness, and relationship maintenance difficulties, while video chat was positively associated with all three. Moderation analyses suggested that other factors (i.e., SIP, age) influenced the strength of association between modalities (i.e., face-to-face, email, social media) and outcomes. The theoretical implications for MRT and the practical implications for mediated sociality during the early stages of the COVID-19 pandemic are discussed.